O ensino da língua inglesa e o trabalho remoto emergencial docente em tempo de pandemia: um estudo na perspectiva da complexidade - Leonardo Rodrigo Soares (2023)
This research aims to verify how the Complex Emergency Conditions were established in the teaching work of 6 English language teachers in the pandemic context. For this, it was observed how the practices mediated by the digital media of these 6 elementary and high school teachers, from state public schools in São João Del Rei, in Minas Gerais, were affected by the Emergency Remote Teaching (ERE). For this purpose, an online semi-structured questionnaire and a semi-structured interview via the Zoom platform were used as a data collection method, in order to observe the teachers’ reality and explore their work in the face of the pandemic. The data were analyzed and interpreted in the light of the complex Emergency Conditions of a Complex Adaptive System, that is, Internal Diversity, Redundancy, Neighbor Interactions, Decentralized Control and Enabling Constraints, proposed by Davis and Simmt (2003) and Davis and Sumara (2006). It was found that these conditions contributed to understanding the possible patterns that emerged from the various relationships that occurred between the different agents mediated by digital media, that is, partnership between teachers in the preparation of materials; clarification of doubts between teachers and students; interns’, monitors’ and school supervision’s contributions; help from the teachers’ children in the use of digital technologies; among others, that go beyond the limits of the classroom. Regarding the control of the system, it was verified that during the ERE there was a repetition of a centralized architecture and, it cannot be said that the control was totally decentralized, since the teachers could not contribute with their opinions and collaborate in the decisions of the operation of the ERE, as they had to follow the guidelines of the Education Department of Minas Gerais State and compulsorily use the Tutored Study Plans (PETs) mediated by digital media – redundant and important elements in the analyzed system. Furthermore, the restrictions established in the ERE were important to guarantee the continuity of school activities to teachers and students. However, the teachers had to adapt their work to the established rules, re-planning their disciplines with the mediation of digital technologies; and to improvise quick solutions in a short period of time, in order for the system to adapt to the emerging needs of the pandemic context of physical distancing and restrictions imposed during the pandemic.